Utilizing near-infrared technology to assess changes in corn silage dry matter and the effects of feeding a starling resistant supplement to dairy cattle - Blackburn, Jarrod Jeffrey (Kansas State University, 2019)
Two studies were conducted that focused on either the accuracy of hand-held near infrared spectrophotometer (NIR) units and two on-farm testing methods compared to conventional 105°C oven drying of corn silage or the use of a starling resistant supplement in total mixed rations (TMR) for lactating dairy cattle. Study 1 evaluated the accuracy of three NIR units (Digi-Star Moisture Tracker, Topcon Agriculture, Fort Atkinson, WI), food dehydrator (FD) (Nesco®, Two Rivers, WI), and a Koster Tester (KT) (Koster Moisture Tester, Inc., Brunswick, OH) to conventional 105°C forced air oven drying. Samples were taken at four Kansas dairy farms and analyzed for DM daily for 20 d. Two calibrations were tested within each NIR unit: NIRu was the DM predicted from the factory-preset calibration, and NIRc was a bias-adjusted DM prediction based on the average difference of oven-dried corn silage and NIRu over the 20-d study. Average oven DM of corn silage was 38.38% ± 0.59 for the 20-d experiment. All three NIRu measurements were lower (P<0.05) than the oven value. While all 3 NIRc predictions were similar (P>0.05) to oven value. KT value was similar (P>0.05) to the oven, while FD value was over estimated DM. (P<0.05). The hand-held NIRS units accurately predicted DM content of the corn silages when the factory preset calibrations were corrected for bias. While the food dehydrator over-estimated the DM of the corn silage and the Koster Tester accurately predicted DM. Study 2 was designed to evaluate the lactation performance of post-peak dairy cattle when using a starling resistant grain supplement. Sixteen prim- and multiparous Holstein cows were housed individually in a tie-stall barn, milked 3x daily, and fed 2x daily. Cows were fed two nutritionally similar diets: 1. TMR with grain in mash form and 2. TMR with grain supplement in a pellet with a 0.953-cm diameter. This study was designed as a single reversal experiment with two 14 d periods with the first 7 d used for an adaptation period and the last 7 d used for data collection in each period. Dry matter intake (DMI), water intake, and milk production was recorded daily. Feed ingredients, TMRS, refusals, and milk samples were collected the last 3 d of each period for analysis. TMRs and refusals were analyzed for particle size distribution with a Penn State Particle Separator. The pelleted supplement had a higher (P<0.05) percentage of DM retained on the 8.0-19.0mm sieve than the mash supplement as the pellet diameter was >8.0mm and could not pass through that sieve. There was no effect of diet (P>0.05) for DMI, feed efficiency, milk component percentage, and protein yield. There was a diet effect (P<0.05) for milk production, fat-corrected milk, energy-corrected milk, solid-corrected milk, and fat yield with lower observed values when cows were fed the pelleted supplement. This leads to the conclusion while a 0.953-cm diameter pellet will reduce starling consumption, it may result in lower milk production of post-peak Holstein cows.
Keywords: Forage; Feed moisture; Pellet; Bird; Grain; 105°C oven